Proyecto de inversión para la implementación de un espacio deportivo con canchas sintéticas en el cantón Catamayo - Quiñones Torres, Mayra Alejandra (2016)
This project aims to establish the growth of business culture through the "investment project for the implementation of a sports area with synthetic courts in the canton Catamayo" the same which will aim sport inclusion in the discipline of Indor, considering which it is the most in demand within the canton. It is a project that targets the economically active population, to insert a new business proposal, called "Camping Sport" For the implementation of this project methodology, techniques and information sources for sustenance and development of it was used. Initially the market study was developed with a sample of 389 surveys of the economically active population of the city of Catamayo, the same as that of a total of 15,026 people there is a real demand for 9,156 and this is how I throw that there is an unmet demand 16,196 equipment The technical study by locational factors was determined to be located south of the canton and which operate 15 hours a day for 312 days a year giving an installed capacity 9360 games a year. The initial investment is determined by the economic study reaching an amount of $ 150,629.14 which the fixed asset account is the most 5 representative in the amount of $ 147,324.80 as the purchase of property and construction of facilities was made. Financial evaluation indicators as was applied: cash flow, VAN has a value of $ 125,504.81, while the TIR is 35.01% higher than the cost of our opportunity is 12% rate; in relation benefit cost will be $ 2.43 leaving a profit of $ 1.43 for every dollar invested and sensitivity analysis is a variation of increase in costs by 53.78% and declining income minimal variation 22.16 %; tools that facilitated the determination of the feasibility of the project Finally conclusions and recommendations are set rescuing the most important and decisive points of the project the project.